The impact of accounting information systems on performance management in the banking sector - Khalid, Bilal; Kot, Michal (My University, 2021)
This study investigated the impact of Accounting Information Systems (AIS) on performance management in Thailand's banking sector. The study was necessitated by the need to understand the financial performance of banks in Thailand in application of advanced management techniques, business developments, growth of the current contemporary business environment and the intensive competitive business environment in the banking sector. The research used purposive sampling to content analyze the financial statements of six major commercial banks in Thailand from 2011-2019. These banks include the Siam Commercial Bank Public Company Limited, Krung Thai Bank Public Company Limited, Bangkok Bank Public Company Limited, Bank of Ayudhya Public Company Limited, Thanachart Bank Public Company Limited, and Kasikorn Bank Public Company Limited. The study comprised of four independent variables representing the AIS: Total Assets, Operational Assets, Total Liabilities and Earning After-Tax; and one dependent variable of Return on Equity. Correlations and multiple regressions were applied to answer the study hypotheses. The results of the study indicated that Total Assets, Operating Assets and Earnings after Tax have a positive and significant effect on Return on Equity. Additionally, Total Liabilities were found to have a negative and significant relationship with Return on Equity. Overall, the study found that AIS has a significant and positive effect on performance management, and the study recommended that AIS should be considered as a critical aspect if long-term growth in performance management is a business objective of the organization.
Keywords: Accounting information system; Banking; Organizational performance; Performance management; Return on equity